Implications for Social Impact of Dialogic Teaching and Learning - García-Carrión, Rocío; López de Aguileta, Garazi; Padrós, Maria; Ramis-Salas, Mimar (Frontiers in Psychology, 2020)
The science of dialogic teaching and learning has especially flourished over the last four decades across age-groups, cultures and contexts. A wide array of studies has examined the uniqueness of dialogue as a powerful tool to lead effective instructional practices, transform the socio-cultural context and people’s mindsets, among many others. However, despite the efforts to extend the benefits of this approach, certain difficulties exist which have hindered the consolidation of dialogic pedagogies in the classroom. This review discusses the implications for social impact of the scientific developments on dialogic teaching and learning. Particularly, an overview of the state of the art on dialogic education is presented. Social improvements in academic attainment and social cohesion are some of the fundamental issues discussed. Those are especially relevant to address crucial needs in education and solve some of the most pressing social problems. A communicative mix-methods approach emerges as one of the critical aspects of this field of research in educational psychology to achieve social impact. Some limitations, such as teachers sustaining different forms of monologic discourse, and challenges for a broader impact are discussed in this review.